A review on well integrity issues for CO2 geological storage and enhanced gas recovery. (June 2016) - Bai, Mingxing; Zhang, Zhichao; Fu, Xiaofei
Abstract: The world's rapid economic growth has contributed to the ever increasing demand for energy which results in the increase of fossil fuels usage. On the other hand, renewable energies, which are considered environmentally friendly, cannot replace the fossil fuels in the short term. For this, CO2 capture and storage (CCS) technologies could work as transitional technology. To ensure a meaningful underground storage, well integrity is potentially the greatest challenge. On one hand, the injected CO2 may cause severe corrosion to metallic tubulars and cement in the wellbore. Identification, quantification and mitigation of this corrosion are the key to achieve satisfactory well conditions. On the other hand, the mechanical integrity loss due to cyclic and thermal loading in the well life will also occur, so to investigate and evaluate well integrity is of paramount importance to ensure a safe operation and storage. This paper presents a definition of well integrity in the scope of CSEGR as well as the mechanisms of well integrity loss. Overview on corrosion issues of metallic and cement corrosion along with the remedial measures is discussed. Through a thorough literature review, well integrity criteria for new and old wells are introduced to provide a guidance for material selection for the usage in CSEGR. Moreover, in order to evaluate the integrity of operational and abandoned wells, this paper provides a review on the existing monitoring methods, as well as risk based methods such as FEPs analysis, Performance and Risk Management, CO2 -PENS, and put forward a new concept of well integrity evaluation.